1998
DOI: 10.1063/1.122683
|View full text |Cite
|
Sign up to set email alerts
|

Structural disorder induced in hydrogenated amorphous silicon by light soaking

Abstract: We show, using variable coherence transmission electron microscopy, that light soaking of amorphous hydrogenated silicon thin films leads to structural changes. We speculate that the structural changes are associated with instability in the as-deposited material. We suggest that improved immunity to Staebler-Wronski degradation could be achieved by a less-ordered material which is closer to the ideal continuous random network. © 1998 American Institute of Physics. ͓S0003-6951͑98͒02947-7͔The light-induced creat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(34 citation statements)
references
References 24 publications
2
32
0
Order By: Relevance
“…16 Fluctuation microscopy on thin films of a-Si and a-Ge indicate that both materials have significant ordering on a length scale of ϳ15 Å, 14 and that this order decays on thermal annealing 17 ͑for a-Ge͒ and on exposure to light 18 ͑for hydrogenated amorphous silicon͒. In contrast to the CRN model, our recently proposed paracrystalline ͑PC͒ model of amorphous semiconductors exhibits MRO that is in qualitative agreement with the fluctuation microscopy data.…”
Section: Introductionsupporting
confidence: 42%
“…16 Fluctuation microscopy on thin films of a-Si and a-Ge indicate that both materials have significant ordering on a length scale of ϳ15 Å, 14 and that this order decays on thermal annealing 17 ͑for a-Ge͒ and on exposure to light 18 ͑for hydrogenated amorphous silicon͒. In contrast to the CRN model, our recently proposed paracrystalline ͑PC͒ model of amorphous semiconductors exhibits MRO that is in qualitative agreement with the fluctuation microscopy data.…”
Section: Introductionsupporting
confidence: 42%
“…[25] The MRO in hydrogenated amorphous silicon are also changed by light-soaking. [26] In disordered graphite, FTEM has detected the signature of C 60 in the matrix. [27,28] In amorphous diamondlike carbon, diamond-like clustering increases by annealing up to 600 8C and graphitic clustering appears at higher temperatures.…”
Section: Elemental Glasses (Si Ge C)mentioning
confidence: 99%
“…The degradation in the properties of a-Si:H films, called Staebler-Wronski effect (S-W effect) [4] , has been an obstacle to the wide spread applications of this material. It is reported that light soaking or high-energy-particle irradiation made the amorphous network of a-Si:H films to be reorganized, leading to a change in the structural order of the films [5][6][7][8][9] . The local distortions of amorphous network due to higher density defects in the irradiated a-Si:H films result in a change of structural order [9] and a macroscopic volume expansion [10] .…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that light soaking or high-energy-particle irradiation made the amorphous network of a-Si:H films to be reorganized, leading to a change in the structural order of the films [5][6][7][8][9] . The local distortions of amorphous network due to higher density defects in the irradiated a-Si:H films result in a change of structural order [9] and a macroscopic volume expansion [10] . Chini et al [11] have reported the formation of 50-260 nm a-Si:H layers on the high-energy-particle-irradiated crystalline silicon surfaces by means of transmission electron microscopy, despite the fact that the penetration depth of high energy particles in crystalline silicon was far beyond the formed amorphous-layer thickness.…”
Section: Introductionmentioning
confidence: 99%